2012
DOI: 10.1080/09658416.2011.598527
|View full text |Cite
|
Sign up to set email alerts
|

EFL learners’ awareness of metonymy–metaphor continuum in figurative expressions

Abstract: Most studies about figurative language learning focus on metaphor rather than metonymy; however, the interactions of metonymy and metaphor are so intricate that the boundary forms not a dichotomy but a continuum. Such a continuum and its influences on figurative language learning have not been studied in depth. The present study investigates EFL (English as a Foreign Language) learners' responses to different metonymic and metaphoric expressions. Twenty-eight Taiwanese EFL learners participated in the study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…teaching idioms (e.g. Conklin & Schmitt, 2008;Cieślicka, 2006;Underwood, Schmitt & Galpin, 2004;Boers, 2000;Chen & Lai, 2013) With respect to learning formulaic sequences, idiomatic expressions have been controversial and challenging that even highly L2 learners avoid using non-compositional idioms (Grant & Bauer, 2004;Siyanova & Schmitt, 2007). Grant and Bauer (2004, p. 50) conclude that "understanding figurative language involves taking a compositional untruth and extracting probable truth from it by an act of pragmatic reinterpretation", suggesting that interpreting the meanings of non-compositional idioms involve both linguistic competence and The Learner' Levels of Collocation Knowledge and Idiomatic Expressions: Exploring the Relationship of Acquisition of Two Items of Phraseology 41 pragmatic competence.…”
Section: Idiom Learning In Non-native Speakersmentioning
confidence: 99%
See 1 more Smart Citation
“…teaching idioms (e.g. Conklin & Schmitt, 2008;Cieślicka, 2006;Underwood, Schmitt & Galpin, 2004;Boers, 2000;Chen & Lai, 2013) With respect to learning formulaic sequences, idiomatic expressions have been controversial and challenging that even highly L2 learners avoid using non-compositional idioms (Grant & Bauer, 2004;Siyanova & Schmitt, 2007). Grant and Bauer (2004, p. 50) conclude that "understanding figurative language involves taking a compositional untruth and extracting probable truth from it by an act of pragmatic reinterpretation", suggesting that interpreting the meanings of non-compositional idioms involve both linguistic competence and The Learner' Levels of Collocation Knowledge and Idiomatic Expressions: Exploring the Relationship of Acquisition of Two Items of Phraseology 41 pragmatic competence.…”
Section: Idiom Learning In Non-native Speakersmentioning
confidence: 99%
“…The author reported that metaphoric awareness is enhanced to interpret figurative usages of expressions and the results supported pedagogical approach to raise awareness among learners in the identification of metaphoric themes. Some empirical evidence adopting the cognitive approach was spotted by (Chen & Lai, 2013) who present a study with the focus on the role of conceptual metaphor with Taiwanese EFL learners at college level. Due to the lack of massive amount of exposure to the target language, Chen and Lai (2013, p.18) concluded that using conceptual metaphors for a typical EFL context is "dependable clues in comprehending and learning idiomatic expressions".…”
Section: Idiom Learning In Non-native Speakersmentioning
confidence: 99%
“…Thus, untangling how L2 learners process L2 metaphors could have important insights for those trying to teach a second language (Littlemore, 2009 , 2019 ). There has been a great body of literature exploring relationships between metaphors processing and second language learning in terms of conceptual metaphor theory (Yasuda, 2010 ; Lu and Sun, 2017 ), metaphorical competence (Danesi, 1993 ; Littlemore and Low, 2006 ), metaphor awareness (Guo, 2007 ; Chen and Lai, 2012 ; Boers, 2013 ), imagery (Ifantidou and Hatzidaki, 2019 ) and individual differences (Johnson and Rosano, 1993 ; Wegner et al, 2020 ). Previous ERPs studies on bilingual metaphor processing found neural similarities and difference in metaphor processing between L1 and L2 (Dong, 2013 ; Park and Chung, 2013 ; Xue et al, 2014 ; Liu, 2016 ; Jankowiak et al, 2017 , 2021 ; Wang, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1980s, metonymy and metaphor have been widely accepted as different ways of thinking rather than as mere stylistic devices (Lakoff and Johnson, 1980 ; Panther and Radden, 1999 ; Dirven, 2003 ; Littlemore, 2019 ) and have received considerable attention within the studies across languages and cultures (Buchowski, 1996 ; Sakuragi and Fuller, 2003 ; Chen and Lai, 2012 ). As two modes of conceptualizing the world, they often interact with each other, prompting Goossens ( 1990 ) to offer the neologism: metaphtonymy.…”
Section: Introductionmentioning
confidence: 99%